Does Virtual Reality Feedback at Infra-Low Frequency Improve Centralized Pain With Comorbid Insomnia While Mitigating Risks for Sedative Use Disorder?: A Case Report - Orakpo, Nnamdi; Yuan, Chujun; Olukitibi, Olanrewaju; Burdette, Jeff; Arrington, Kim (Frontiers in Human Neuroscience, 2022)
This case reports a patient with clinically diagnosed moderate-severe insomnia secondary to chronic lower back pain and sciatica, previously treated with hydrocodone, naproxen, cyclobenzaprine and nightly diazepam. He underwent a trial of 20 sessions of virtual reality neurofeedback therapy (VR-NFB) at the Infralow frequency, and by the end of 20 sessions achieved sustained analgesia and consequently, a complete resolution of his pain-related insomnia. At one year, follow up confirmed his improvements were sustained, and he maintained his abstinence from sedatives as observed on the Prescription Monitoring Program for controlled substances. This case highlights the importance of understanding chronic pain and its correlation to restorative sleep, while incorporating endogenous neuromodulation in behavioral sleep medicine, helping mitigate the risk of benzodiazepine use disorder. This may be the first case of complete resolution of chronic pain with comorbid insomnia after treatment with VR-NFB at the Infralow frequency.